THE RELATIONSHIP SELF-FORGIVENESS WITH QUALITY OF LIFE IN HIV / AIDS PATIENTS AT POLYCLINIC VCT MOJOKERTO REGENCY - Indah Lestari; catur Prasastia lukita Dewi; Riska Aprilia (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
ABSTRACT The number of people with HIV / AIDS is like an iceberg, which appears to be only a small part. At present, HIV cannot be cured. This condition has a comprehensive impact on patients. Through Self-forgiveness, it is expected that patients can reduce negative feelings or emotions, so that they will be motivated to change their behavior for the better. The research objective proved the relationship self forgiveness with quality of life in HIV/AIDS patients. The research design was analytic correlation with Cross Sectional approach. The Sample was all patient of HIV / AIDS (selected who were diagnosed with HIV / AIDS because of sexual relations) who undergoing treatment in Polyclinic VCT Mojokerto Regency amounting to 122 people, with consecutive sampling. The independent variable was self forgiveness and the dependent variable was quality of life in HIV/AIDS patients. The instrument used a HFS (Heartland Forgiveness Scale) questionnaire for self-forgiveness. WHOQOL-HIV BREF for quality of life. The result of Spearman-Rho Correlation showed significant = 0.000, so a positive relationship between Self-Forgiveness and Quality of Life in HIV / AIDS. Respondents who have high self-forgiveness, also have a good quality of life, as many as 55 respondents (44.8%) and very good, that is as many as 25 respondents (20.7%). Forgiveness can affect the physical health of individuals and the factors that affect self-forgiveness, namely, the emergence of empathy, emotional intelligence, self-reflection, and personality characteristics. Improvement of quality of life can occur if the HIV / AIDS patient has been able to accept his condition, transforming himself into an open person and always apply the forgiveness attitude and can forgive or forgive the incident ever done by himself or others, so as to neutralize the negative feelings into positive. Keywords: Self Forgiveness. Quality of Life, HIV/AIDS